2020
DOI: 10.4018/978-1-7998-0111-5.ch004
|View full text |Cite
|
Sign up to set email alerts
|

Migration Policy and Problems of Ensuring Economic Security of Countries

Abstract: In this chapter the authors consider the impact of migration processes on the state of their home country's security. The other actual direction of this research is to identify the dependence of the country's economic security on the intensity of migration regulation. The complexity of assessing global trends in migration policy leads to the need for a comparative analysis of the conditions for their implementation in the context of world labor migration centers. The chapter analyzes the main tools of migratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Moreover, some migrants may use Russia as a transit stop for further migration to other countries (Rybakovsky and Ryazantsev 2005). Previous studies have suggested that Russia is both a donor country and a recipient country (Di Bartolomeo et al 2014;Podolskaya et al 2020) for migration among the general population. However, scholars who have taken the characteristics of migrants into account have argued that Russia is more of a donor country (Kolesnikova et al 2014;Ushkalov and Malakha 2001;Zubova 2012); i.e., that it is a country on the losing side of the international exchange of highly skilled individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some migrants may use Russia as a transit stop for further migration to other countries (Rybakovsky and Ryazantsev 2005). Previous studies have suggested that Russia is both a donor country and a recipient country (Di Bartolomeo et al 2014;Podolskaya et al 2020) for migration among the general population. However, scholars who have taken the characteristics of migrants into account have argued that Russia is more of a donor country (Kolesnikova et al 2014;Ushkalov and Malakha 2001;Zubova 2012); i.e., that it is a country on the losing side of the international exchange of highly skilled individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some migrants may consider Russia as a transit stop for further migration to other countries [32]. Previous studies suggest that Russia is both a donor country and a recipient country [11,29] for migration in general. If the characteristics of migrants are taken into account, Russia is suggested to be more of a donor country [36,39,17], i.e.…”
Section: Introductionmentioning
confidence: 99%